Peran Orang Tua dengan Hambatan Pendengaran dalam Pengasuhan Anak Dengar - Kadek Sri Kermawaty; Bayu Pamungkas; Wahyu Setyoadi Nugroho (Dinasti Research, 2026)
This study aims to identify and analyze the role of parents with hearing impairments in raising hearing children. The research focuses on three aspects: educating and guiding children, disciplining and instilling responsibility, and fulfilling children's psychological, social, and emotional needs. This study employed a qualitative case study design involving six families with parents who have hearing impairments in Yogyakarta and its surrounding areas. Data were collected through participant observation, in-depth interviews, and documentation. Data validity was ensured through source, technique, and time triangulation, as well as member checking. The findings show that parents educate and guide hearing children by using visual communication, sign language, writing, concrete objects, digital media, and learning assistance from extended family or the surrounding community. Discipline and responsibility are developed through habituation, visual rules, repeated messages, role modeling, daily monitoring, and concrete consequences. Psychological, social, and emotional needs are fulfilled through affection, protection, acceptance, physical closeness, attention, and support for the child's identity as a Child of Deaf Adults (CODA). The study concludes that hearing impairment does not prevent parents from performing meaningful parenting roles when supported by bilingual-bimodal strategies, extended family involvement, technology, and a disability-friendly environment